Analisis Media Cetak Harian Banyuasin Dalam Penggunan Bahasa Jurnalistik (Studi Berita Pada Edisi April 2022) - Nadya Dwi Handayani; Fifi Hasmawati; Anang Walian (CV. ITTC INDONESIA, 2024)
This research entitled Analysis of Banyuasin Daily Print Media in the Use of Journalistic Language (News Study in April 2022 Edition) is motivated by the problem of writing news that is not in accordance with the rules in the Journalistic Language Code of Ethics. The aim to be achieved in this study is to find out how the application of journalistic language in the headlines of the Banyuasin Daily Newspaper. The research method used is using a qualitative approach. Meanwhile, the type of data uses primary data and secondary data with data collection through interviews, observation and documentation. In addition, data analysis techniques use data reduction, data presentation and data verification and are followed by checking the correctness of the data.The research approach that the author uses is a Qualitative Approach. Qualitative research is research used to examine the conditions of natural objects where the researcher is the core instrument. This research also consists of humans, events, documentation. Human data sources are in the form of words and actions of people who can provide data through interviews, observations, and documents. The results of the research and it can be concluded that the Banyuasin Banyuasin Daily Newspaper still found errors in the use of journalistic language such as spelling errors and lack of economy in writing, but for sentence effectiveness, the Banyuasin Daily Newspaper has fulfilled the rules of journalistic language.